2013
DOI: 10.3389/fmicb.2013.00307
|View full text |Cite
|
Sign up to set email alerts
|

Influenza A(H1N1)pdm09 virus and asthma

Abstract: Respiratory viral infection is a major cause of asthma exacerbations in both children and adults. Among the respiratory viruses, influenza virus is a particularly important pathogen due to its enormous morbidity and mortality in annual epidemics. The swine-origin influenza A virus, designated as A(H1N1)pdm09, emerged in the spring of 2009 and caused the first influenza pandemic in the 21st century. With the emergence of the novel A(H1N1)pdm09 virus, numerous epidemiologic studies detected asthma as a frequent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 34 publications
0
19
0
1
Order By: Relevance
“…These upper respiratory tract infections frequently lead to hospital admission for asthma patients (97). Interestingly, asthma was the most common comorbidity among hospitalized patients during the 2009 H1N1pdm IAV pandemic (98)(99)(100)(101). A state of hyperresponsiveness in the asthmatic patients, as well as increased levels of inflammatory molecules (e.g., histamine, IL-6, and leukotriene), are believed to contribute to asthmatic exacerbation from viral infection (102).…”
Section: Role Of Mast Cells In Allergies and Asthmamentioning
confidence: 99%
“…These upper respiratory tract infections frequently lead to hospital admission for asthma patients (97). Interestingly, asthma was the most common comorbidity among hospitalized patients during the 2009 H1N1pdm IAV pandemic (98)(99)(100)(101). A state of hyperresponsiveness in the asthmatic patients, as well as increased levels of inflammatory molecules (e.g., histamine, IL-6, and leukotriene), are believed to contribute to asthmatic exacerbation from viral infection (102).…”
Section: Role Of Mast Cells In Allergies and Asthmamentioning
confidence: 99%
“…Moreover, consecutive asthma exacerbation was also reduced in vaccinated children with asthma. Although the effectiveness of A(H1N1)pdm09 vaccines are widely reported [9][10][11][12], there are few reports that discuss the effectiveness in patients with asthma [19,44,45]. To our knowledge, ours is the first investigation to focus on differences in the effectiveness of vaccination for PDIA with mild to moderate ILI between children with and without asthma and consecutive asthma exacerbation related to influenza A(H1N1)pdm09 infection.…”
Section: Discussionmentioning
confidence: 88%
“…Kloepfer et al [16] showed that children with asthma had increased susceptibility for A(H1N1)pdm09 infection compared to children without asthma, which was concluded before widespread A(H1N1)pdm09 vaccine release to avoid confounding results with immunological effects of the virus and false positive test results resulting from use of the live virus vaccine. Although the effectiveness of A(H1N1)pdm09 vaccines are widely reported [9,10,, there are few reports that discuss the effectiveness in patients with asthma [19,44,45].…”
Section: Introductionmentioning
confidence: 99%
“…Respiratory viral infection is a major cause of "Asthma" and "Tissis" in both children and adults [32]. Among the respiratory viruses, influenzavirus is a particularly important pathogen due to its enormous morbidity and mortality in annual epidemics [33]- [35].…”
Section: Efficacy Range and Theoretical Foundationmentioning
confidence: 99%